Adult leadership and the development of Children's Spirituality: exploring Montessori's concept of the prepared environment. Issue 4 (2nd October 2019) - Bennetts, Karen; Bone, Jane
ABSTRACT: This article explores Montessori's concept of the Prepared Environment, which includes adult leadership, as an important contribution to the field of Children's Spirituality. Montessori elevated the spiritual development of children to a central place in social life. She advocated preparation of the teacher as a community leader who works through the environment to guide a pedagogically-oriented process that underpins spiritual development. This model of leadership offers the child a reciprocal relationship with the Prepared Environment, which operates as the child's true teacher. The preparation of the adult, as an element of the Prepared Environment, has a spiritual tone and is a key aspect of Montessori science and philosophy, designed to support the holistic development of the child as both a hope and a promise for human beings.